Ureterovaginal Fistula: An Audit of Treatment Options in an Underdeveloped Area of Pakistan - Uzma Aziz, Madiha Afzal, Muhammad Sohail, Nasim Aslam Ghumman, Muhammad Asif, Sabeena Umer, Mufassar Nishat, (Pakistan Journal of Medical & Health Sciences, 2022)
Throughout 2021, we were requested to assess and treat 10 women who had suffered ureterovaginal fistulas after caesarean sections at separate remote hospitals. We describe our experiences diagnosing and treating uninsured patients at a hospital with minimal resources. A three-swab test was conducted on each of the 10 patients, and an abdominal and pelvic ultrasound was utilised to help locate the afflicted ureter. The patient had transvesical ureteral stent insertion. The stent was removed after two weeks. No wetness in the 10 patients.In the middle of today's complicated health care system, we must continuously remind ourselves of the common develops after a caesarean section and a well-known and simple diagnostic technique management in resource-poor communities